Effect of dietary supplementation of turmeric, Curcuma longa leaf on growth and health status of African catfish, Clarias gariepinus - Lee Seong Wei; Kon Yeu Hooi; Martina Irwan Khoo; Azra MN; Wendy Wee (Veterinary Integrative Sciences)
High stocking density poses a risk to an aquaculture species' production and health status, increasing their vulnerability to diseases and infection. Feed additive reportedly enhances the growth and health of farmed fish. Therefore, this study evaluated the effects of turmeric, Curcuma longa, leaf powder on the growth performance, digestive enzyme activity, hematology, antioxidative response, and disease resistance of African catfish. A feeding trial was conducted using a control diet and three experimental diets containing powdered C. longa leaf at various levels (0.5%, 1.0%, and 1.5%). After eight weeks, the growth performance of African catfish supplemented with C. longa leaf powder improved significantly (p <0.05), particularly the fish fed with 1.5% turmeric leaf powder. Meanwhile, the FCR was significantly reduced in the treatment groups compared to the control group, where the CL15 group recorded the lowest FCR. Furthermore, the fish fed 1.5% powdered C. longa leaf had substantially higher (p <0.05) lipase, protease, and amylase activities than other groups. Powdered C. longa leaf supplementation also significantly enhanced (p <0.05) the antioxidative responses of African catfish compared to the control group, particularly glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT). In addition, the cumulative survival rate was significantly (p <0.05) higher in fish that received powdered C. longa leaf,with the highest being the CL15 group. In summary, 1.5% powdered C. longa leaf is possibly the optimal dosage for African catfish feed to boost their productivity.